Hepatoprotective study of Indonesian water kefir against CCl4-induced liver injury in rats - Widhya Aligita; Marlia Singgih; Entris Sutrisno; I Ketut Adnyana (GarVal Editorial Ltda., 2023)
Context: Water kefir is a fermented beverage that is typically made in the home by inoculating a sugar-rich solution with a microbial community (water kefir grains). Several studies on the metabolite content and hepatoprotective effects of water kefir have been published, but carbon tetrachloride (CCl4)-induced acute liver injury has not been studied. Aims: To evaluate the efficacy of water kefir in vivo against hepatoprotective CCl4-induced acute liver injury and to in silico investigate metabolites that play an important role in hepatoprotective mechanisms. Methods: The present study aimed to investigate the hepatoprotective activity of water kefir in an animal model caused by CCl4. Furthermore, using molecular docking, the metabolites found in water kefir were evaluated for their role in the NF-κB and Nrf2 signaling pathways. Results: Water kefir significantly and dose-dependently alleviated acute liver injury caused by CCl4. Water kefir administration at all doses produced results comparable to the positive control (Curcuma extract). Molecular docking simulations showed that, compared to Nrf2, the 25 metabolites were more likely to interact with the NF-kB receptor. Fumaric acid is the strong metabolite that interacts with the NF-κB receptor with a free energy of binding and an inhibition constant of -6.66 kcal/mol and 13.22 µM, respectively. Conclusions: Water kefir administration improved the condition of liver damage, characterized by a decrease in serum levels of AST, ALT, TNF-a, TGF-b, and an improvement in the liver tissue profile. In silico evaluation showed that the metabolites in water kefir were able to interact with target proteins in the NF-kB and Nrf2 pathways. It was concluded that water kefir improves the condition of the liver by reducing the level of necrosis and fibrosis.